Cannabis law - MacFarlane, Bruce A. (Thomson Reuters, 2018)
The Cannabis Act : history and overview -- The federal regulatory framework -- Search and seizure -- The detention, disposition, and forfeiture of seized property -- Cannabis edibles -- Provincial and territorial regulation -- Municipal regulation -- Regulation by Indigenous peoples -- Possession -- Distribution and selling -- Importing/exporting -- Production -- Cannabis-impaired driving -- Using a young person to commit and offence -- Promotion, packaging and labeling -- Evidence and procedure -- Ticketing -- Administrative monetary penalties -- Sentencing and criminal records -- Medical cannabis -- Workplace and human rights-related issues -- Commercial law issues.